Chemical Composition, Toxicity, Antinociceptive, and Anti-Inflammatory Activity of Dry Aqueous Extract of Varronia multispicata (Cham.) Borhidi (Cordiaceae) Leaves - Lopes, Klaylton; Oliveira, Juliana; Sousa-Junior, Fabio J. C.; Santos, Túlio da F.; Andrade, Débora; Andrade, Sara L.; Pereira, Washington L.; Gomes, Paulo Wender P.; Monteiro, Marta C.; e Silva, Consuelo Y. Yoshioka; da Silva, Milton Nascimento; Maia, Cristiane F.; et al. (Frontiers in Pharmacology, 2019)
Varronia multispicata (Cordiaceae), an herbaceous plant distributed in tropical and subtropical regions and native of Brazil, is widely used in folk medicine to treat respiratory and digestive diseases, inflammation and some types of infections. Thus, this study aimed to investigate acute oral toxicity, antinociceptive and anti-inflammatory activities of dry aqueous extract of V. multispicata (AEVm) and to identify its compounds. Extract was obtained by lyophilized leaf infusion and their composition was analyzed by ultra-performance liquid chromatography-high resolution mass spectrometry (LC-MS). Acute oral toxicity was evaluated in female rats treated with AEVm (2,000 mg/kg) in a single oral dose. Mortality, body weight changes, feed and water intake, organ weights, histological and biochemical parameters were screened for 14 days. Antinociceptive activity was evaluated by writhing (WT), formalin (FT) and hot plate (HP) tests in male mice while anti-inflammatory activity was performed by carrageenan (CPE) and dextran (DPE) -induced paw edema tests and carrageenan-induced peritonitis (CP) test in male rats. Additionally, spontaneous open-field (OF) locomotion was evaluated. LC-MS revealed the presence of flanonoids with biological activity. In toxicity evaluation, extract did not cause deaths in dose of 2,000 mg/kg, and there were no significant behavioral, histological or biochemical alterations. Additionally, evidence of hepatoprotective and antioxidant activity was observed. In pharmacological evaluation AEVm showed dose-dependent antinociceptive activity in WT, with a median effective dose of 146.89 mg/kg, which showed selectivity by inflammatory base processes (FT first phase), showing no activity in neuropathic nociception components (FT second phase and HP) or about consciousness and locomotion in OF. AEVm also showed significant anti-inflammatory activity, inhibiting CPE and cell migration and NO production in CP test. These data demonstrate that AEVm has low oral toxicity – with evidence of hepatoprotective and antioxidant properties –, antinociceptive and anti-inflammatory activity, supporting V. multispicata traditional use, possibly related to flavonoids present in its constitution.